Linguistische kontrastive Studien Deutsch-Thailändisch: Eine Bestandsaufnahme - Attaviriyanupap, Korakoch (Linguistik Online, 2009)
This article is a survey and synthesis of German-Thai linguistic contrastive studies conducted between 1978 and 2008. Its objective is to give an overview of linguistic contrastive studies on these two languages. The first part is the analysis and synthesis of all these Thai-German linguistic contrastive studies in terms of quantity, characteristics and researched topics as well as the methodology used. In the second part, all relevant factors leading to this resulted overall picture are discussed and suggestions for further development in this field of study are made.